KAMPOENG PELANGI: KAMPUNG VERTIKAL UNTUK MASYARAKAT BERPENGHASILAN RENDAH - Alvin Alvin; Franky Liauw (Jurusan Arsitektur dan Perencanaan, 2021)
A worrying symptom and supporting environmental imbalance is high population growth. The existence of population growth makes the need for housing continues to increase, the problem is that the facilities provided by the government and developers can only be reached by the upper middle class, while every resident should have the right to have a place to live, including low-income people (MBR). The culture and traditions of the people of a village that are thick with activities and their lives are fading after the development towards vertical, closed and individualistic dwellings. Kalianyar is the most densely populated area in DKI Jakarta, living in the midst of crowds has become a daily pastime. In addition to the natives, many migrants from outside Jakarta and Java chose Kalianyar, Tambora as their temporary residence. It is undeniable that the population density in Kalianyar creates housing problems and the demand for housing. Therefore, Kampoeng Pelangi is here to make the lives of Kalianyar residents better, more beautiful and harmonious. create a vertical residence with a flexible architectural approach and sustainable development that can reflect, improve and fulfill the needs and life of a village in the Kalianyar Village area. Implementing sustainable living in social, economic, and environmental aspects in the form of a vertical village and applying flexible architecture in the form of space flexibility. Keywords: Flexible; MBR; Population growth; Sustainable Development; Vertical Village Abstrak Gejala yang mengkawatirkan dan mendukung ketidak seimbangan lingkungan hidup adalah pertumbuhan penduduk yang tinggi. Adanya pertumbuhan penduduk membuat kebutuhan akan hunian terus meningkat, permasalahannya fasilitas yang disediakan oleh pemerintah dan pengembang hanya dapat dijangkau oleh kalangan menengah keatas saja, sedangkan seharusnya setiap penduduk memiliki hak untuk memiliki tempat tinggal tak terkecuali masyarakat berpenghasilan rendah (MBR). Kebudayaan dan tradisi masyarakat sebuah kampung yang kental dengan aktivitas dan kehidupannya semakin pudar setelah perkembangan ke arah hunian-hunian yang vertikal, tertutup dan individualistik. Kalianyar merupakan daerah terpadat di DKI Jakarta, hidup di tengah kesesakan sudah jadi lahapan sehari-hari. Selain warga asli, banyak pula pendatang dari luar Jakarta dan Jawa yang memilih Kalianyar, Tambora sebagai wilayah untuk mereka tempati sementara. Tak dipungkiri bahwa kepadatan penduduk di Kalianyar menimbulkan permasalahan-permasalahan hunian dan permintaan rumah tinggal. Maka dari itu, Kampoeng Pelangi hadir untuk membuat hidup warga Kalianyar lebih baik, indah dan harmoni. membuat sebuah hunian vertikal dengan pendekatan arsitektur fleksibel dan pembangunan berkelanjutan yang dapat mencerminkan, meningkatkan dan memenuhi kebutuhan dan kehidupan sebuah kampung di daerah Kelurahan Kalianyar. Menerapkan hidup yang berkelanjutan dalam aspek sosial, ekonomi, dan lingkungan dalam rupa kampung vertikal serta menerapkan arsitektur fleksibel dalam wujud fleksibilitas ruang.